Effect of renal function on the pharmacokinetics of fimasartan: a single-dose, open-label, Phase I study - Kim S; Lee J; Shin D; Lim KS; Kim YS; Jang IJ; Yu KS (Dove Medical Press, 2014)
Seokuee Kim,1 Jongtae Lee,1 Donghoon Shin,1 Kyoung Soo Lim,1 Yon Su Kim,2 In-Jin Jang,1 Kyung-Sang Yu1 1Department of Clinical Pharmacology and Therapeutics, 2Division of Nephrology, Department of Internal Medicine, Seoul National University College of Medicine and Hospital, Seoul, KoreaBackground: Fimasartan is a novel angiotensin II receptor blocker. Fimasartan is mainly eliminated via biliary excretion, and its urinary elimination is less than 3%.Objective: Based on guidance from the United States Food and Drug Administration, a reduced pharmacokinetic (PK) study was conducted to evaluate the effect of renal function on the PK of fimasartan in patients with renal impairment and healthy volunteers.Methods: A single centre, single-dose, open-label, healthy volunteer controlled trial was conducted in patients with renal impairment (RI) (estimated glomerular filtration rate lower than 30 mL/min/1.73 m2) and age-, weight- and sex-matched healthy volunteers (estimated glomerular filtration rate higher than 90 mL/min/1.73 m2). All participants received a single oral dose of fimasartan 120 mg, after which serial blood sampling for PK evaluation was conducted. Noncompartmental PK analysis of fimasartan was performed. A mixed-effects model approach was used to identify significant covariates and PK parameters.Results: Sixteen subjects were enrolled (8 healthy volunteers and 8 RI patients). The maximum plasma concentrations and areas under the plasma concentration curves of the RI patients were higher than those of the healthy volunteers, with geometric mean ratios of 1.87 and 1.73, respectively. The relative bioavailability of fimasartan from the population PK analysis was 77% higher in the RI patients than in the healthy volunteers.Conclusion: The increased drug exposure of fimasartan in RI patients was explained by the increased relative bioavailability. This result can be explained from our knowledge concerning alterations in PK related to renal function.Keywords: renal impairment, fimasartan, pharmacokinetics, safety